1996
DOI: 10.1093/oxfordjournals.aje.a008771
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Prenatal Growth among Infants with Cardiovascular Malformations: Possible Fetal Hemodynamic Effects

Abstract: This study characterized fetal growth differences among control infants (n= 276) and infants with d-transposition of the great arteries (TGA) (n = 69), tetralogy of Fallot (n = 66), hypoplastic left heart syndrome (n = 51), and coarctation of the aorta (n = 65), thus permitting assessment of competing theories about the relation between these cardiovascular malformations and fetal growth disturbance. Subjects were liveborn singletons without genetic or extra-cardiovascular structural abnormalities sampled from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
132
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 32 publications
15
132
3
1
Order By: Relevance
“…Poor growth has been associated with genetic and environmental factors, but the prevailing view identifies a hypermetabolic state and malabsorption as common causes (11,12). However, increasing evidence shows that growth abnormalities begin before birth (11)(12)(13), suggesting the contribution of other necessary genetic and environmental factors. The majority of HLHS cases are now diagnosed in utero, contributing to increased survival, and are not typically associated with fetal demise (9,14).…”
mentioning
confidence: 99%
“…Poor growth has been associated with genetic and environmental factors, but the prevailing view identifies a hypermetabolic state and malabsorption as common causes (11,12). However, increasing evidence shows that growth abnormalities begin before birth (11)(12)(13), suggesting the contribution of other necessary genetic and environmental factors. The majority of HLHS cases are now diagnosed in utero, contributing to increased survival, and are not typically associated with fetal demise (9,14).…”
mentioning
confidence: 99%
“…CHD is considered a risk factor for FGR, even in the absence of associated chromosomal abnormalities (15,16). However, the underlying mechanism has not yet been clearly elucidated.…”
Section: Editorialmentioning
confidence: 99%
“…Embryos with intrinsic growth disturbances are at an increased risk of developmental abnormalities during cardiogenesis. Other explanation may be that fetal circulatory patterns in the presence of specific cardiovascular malformations are incompatible with optimal fetal growth [16]. Recently, it has been reported that fetuses with CHD have decreased placental growth factor (PlGF) at 11-13 weeks' gestation (17).…”
Section: Editorialmentioning
confidence: 99%
“…Although SGA takes into account gestational age and sex, it is based on a distribution of a normative population with a distinct cut point at the 10th percentile, and does not account for an individual's or population's growth potential. Intrauterine growth restriction is conceptually straightforward but difficult to delineate clinically because it refers to an in utero environment that leads to a fetus failing to meet its growth potential; the complexity is in assessing “potential.” Defining intrauterine growth restriction is even more perplexing in the population with CHD because growth potential may be debated, given the well‐described lesion‐specific differences in birth weight 5, 6. Steurer and colleagues, in this issue of the Journal of the American Heart Association ( JAHA ), provide further evidence that CHD lesions are associated with lower birth weight for gestational age 7.…”
mentioning
confidence: 99%
“…In CHD, however, assessing symmetry in growth as a marker of an in utero insult is again confounded by lesion‐specific differences. For example, birth weights of infants with tetralogy of Fallot or coarctation of the aorta appear to be more severely affected than birth weights in infants with transposition of the great arteries 6. At the same time, infants with transposition or hypoplastic left‐sided heart syndrome have proportionally smaller heads for their weight at birth compared with infants with tetralogy of Fallot or coarctation, suggesting the mechanism of fetal growth abnormalities diverges by lesion.…”
mentioning
confidence: 99%